2015
DOI: 10.4236/ae.2015.31004
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Night Lighting Reduces Firefly (Coleoptera: Lampyridae) Occurrence in Sorocaba, Brazil

Abstract: Artificial night lighting is gaining attention as a new type of pollution; however, studies of its impacts are scarce. Fireflies provide good models to investigate its effects on nocturnal wildlife, since they depend on their bioluminescence for reproduction. This study investigated the impact of artificial illumination on firefly activity at the new campus of the Federal University of São Carlos (Sorocaba, Brazil). The flashing activity of different firefly species, especially Photinus sp1 (82% of all occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 48 publications
1
22
0
1
Order By: Relevance
“…In another observational study on a university campus in Sorocaba, Brazil, Hagen, Santos, Schlindwein, and Viviani () found that courtship flashing by several firefly species was affected by multi‐metal vapor spotlights illuminating an outdoor sport court. On nights when the spotlights were turned on, flash activity by the most common species, Photinus sp1, was significantly reduced.…”
Section: Firefly Vision and Bioluminescencementioning
confidence: 99%
“…In another observational study on a university campus in Sorocaba, Brazil, Hagen, Santos, Schlindwein, and Viviani () found that courtship flashing by several firefly species was affected by multi‐metal vapor spotlights illuminating an outdoor sport court. On nights when the spotlights were turned on, flash activity by the most common species, Photinus sp1, was significantly reduced.…”
Section: Firefly Vision and Bioluminescencementioning
confidence: 99%
“…During the mating season, adults begin flashing late in the day, when ambient light levels have declined to a species-specific threshold [ 36 , 37 ]. High levels of broad spectrum ALAN can delay or inhibit male signaling activity, and negatively affect female receptivity to bioluminescent signals [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of artificial light on fireflies was studied in many firefly species. Under the light pollution, the abundance of fireflies displayed lower numbers than without lighting [4,9]. Several firefly researchers have considerably examined how the light pollution impacts on the bioluminescent insects especially their courtship and reproduction.…”
Section: Introductionmentioning
confidence: 99%